RANDOMISED DOUBLE-BLIND PLACEBO-CONTROLLED STUDY OF FOLIC ACID ADJUNCT FOR 8 WEEKS IN HYPERHOMOCYSTEINAEMIC HYPERTENSIVE PATIENTS IN ZARIA, NIGERIA - ONYEMELUKWE, Obiageli U; MAIHA, Bilkisu B; AYANWUYI, Lydia O; DAHIRU, Tukur (Journal of Drug Delivery and Therapeutics, 2018)
Objectives: This study was aimed at determining the effect of folic acid adjunct therapy on homocysteine (HCY) and blood pressure (BP) levels in hypertensive subjects. Method: The study was a double blind placebo-controlled trial on 100 hypertensive patients randomised into 50 folate and 50 placebo groups, where the folate group had 5 mg folic acid daily for 8 weeks. Fasting plasma homocysteine, folate and blood pressure levels were determined at baseline, at 4 and at 8 weeks. The Mixed Model Repeated Measures analysis of variance was applied for data analysis. Results: Hyperhomocysteinaemia was found at baseline in the folate (21.3 ± 5.7 µmol/L) and placebo (21.6 ± 4.9 µmol/L) groups which did not differ statistically (p > 0.05). Folic acid adjunct therapy, reduced homocysteine levels at 4 weeks by 2.0 µmol/L (9.2 %, p < 0.05) and at 8 weeks by 1.2 µmol/L (5.6 %, p < 0.05), with no significant (p > 0.05) systolic and diastolic blood pressure lowering effect. High base-line folate levels were found in both folate (113.8 ± 51.2 ng/ml) and placebo groups (109.5 ± 51.4 ng/ml) with no statistically significant difference (p > 0.05). Conclusion: Short-term daily folic acid supplementation over 8 weeks had a significant homocysteine reduction effect with no significant reduction in systolic and diastolic blood pressures of hypertensive subjects in Zaria, Nigeria. Hyperhomocysteinaemia could not be accounted for by suboptimal folate levels. Keywords: Hypertension, Homocysteine, Blood pressure, Folate, Placebo, Nigeria.